Experimental investigation on the debonding failure mode of basalt-based FRP sheets from concrete. (15th November 2018) - Nerilli, Francesca; Vairo, Giuseppe
Abstract: In this paper, the debonding failure mode of basalt-based FRP (BFRP) reinforcements from concrete supports is experimentally investigated. In detail, more than 40 push-pull double shear tests on BFRP-concrete specimens with different geometrical configurations were carried out. Results in terms of debonding load and strain patterns arising at the BFRP layer are presented and discussed, furnishing indications about the influence of: composite thickness, width ratio between the BFRP width and the concrete one, anchor length. On the basis of the proposed experienced evidence, the design indications provided by the Italian Technical Document CNR DT200/R1 and addressing the assessment of the debonding load have been critically analysed. Accordingly and as a further result, a novel effective calibration of the corresponding empirical correction parameter k g (introduced to improve the previsional effectiveness of the fracture-mechanics-based theoretical estimate of the debonding force), has been provided. In detail, in order to ensure the best agreement between proposed experimental data and theoretical predictions associated to concrete elements externally strengthened by the in-situ application of BFRP sheets, the value k g = 0.117 mm ( 5 % fractiles 0.079) is specifically proposed, resulting very different from the indication by the Italian technical document ( k g = 0.077 mm, 5 % fractiles 0.037 mm).